2017
DOI: 10.1155/2017/9172741
|View full text |Cite
|
Sign up to set email alerts
|

4‐Hydroxynonenal Contributes to Angiogenesis through a Redox‐Dependent Sphingolipid Pathway: Prevention by Hydralazine Derivatives

Abstract: The neovascularization of atherosclerotic lesions is involved in plaque development and may contribute to intraplaque hemorrhage and plaque fragilization and rupture. Among the various proangiogenic agents involved in the neovascularization process, proatherogenic oxidized LDLs (oxLDLs) contribute to the formation of tubes via the generation of sphingosine 1-phosphate (S1P), a major mitogenic and proangiogenic sphingolipid mediator. In this study, we investigated whether 4-hydroxynonenal (4-HNE), an aldehydic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 68 publications
0
10
0
1
Order By: Relevance
“…Complexity of the opposing regulatory effects of 4-HNE depending on its amount and the availability of target macromolecules has been revealed in different pathophysiological processes. For example, the 4-HNE mediated neovascularization has concentration dependent effects on redox signaling in a way that low levels of 4-HNE (≤ 1 µM) provoke neovascularization via ROS and activation of sphingolipid pathway, while higher concentration does not have such effects [19]. Similarly, the recent study by Dodson and colleagues has shown that at low concentration (5 -10 µM) 4-HNE specifically targets and modifies proteins involved in the initiation of autophagy, such are mTOR and Beclin1 [20].…”
Section: -Hne Can Mediate Redox Signaling Pathwaysmentioning
confidence: 99%
“…Complexity of the opposing regulatory effects of 4-HNE depending on its amount and the availability of target macromolecules has been revealed in different pathophysiological processes. For example, the 4-HNE mediated neovascularization has concentration dependent effects on redox signaling in a way that low levels of 4-HNE (≤ 1 µM) provoke neovascularization via ROS and activation of sphingolipid pathway, while higher concentration does not have such effects [19]. Similarly, the recent study by Dodson and colleagues has shown that at low concentration (5 -10 µM) 4-HNE specifically targets and modifies proteins involved in the initiation of autophagy, such are mTOR and Beclin1 [20].…”
Section: -Hne Can Mediate Redox Signaling Pathwaysmentioning
confidence: 99%
“…Loss of capillary density and diminished endothelial function occur in pathological hypertrophy [46] , [47] , [48] and have been suggested to play a causal role in idiopathic dilated cardiomyopathy [49] and heart failure with preserved ejection fraction [50] , [51] . Interestingly, reactive products normally detoxified by ALDH2, such as HNE, can promote angiogenesis and augment microvessel density in other tissues [52] , [53] , [54] . Thus, it makes sense that HNE may be important for regulating capillary density in the heart as well.…”
Section: Discussionmentioning
confidence: 99%
“…The catabolism of 4HNE is critically dependent on cellular levels of glutathione‐S‐transferases, alcohol dehydrogenases, and aldehyde dehydrogenases (ALDH)s. There are conflicting findings regarding the effect of 4HNE in coronary ECs. For instance, Camare C et al reported that low doses of 4HNE accelerate tube formation in human microvascular ECs . However, Stagos D et al concluded that 4HNE inhibits tube formation in human bone marrow‐derived ECs .…”
Section: Introductionmentioning
confidence: 99%